Metabolic effects of rapid weight loss in elite athletes - Kukidome, T.; Aizawa, K.; Okada, A.; Tokuyama, K.; Kondo, I. (Japanese Journal of Physical Fitness and Sports Medicine, 2007)
This study examined the effects of resting metabolic rate (RMR), sleeping metabolic rate (SMR), and diet-induced thermogenesis (DIT) during acute weight loss in elite male wrestlers. [Methods] Subjects were elite male wrestlers (n=6), who were instructed to reduce the body weight in seven days. RMR, SMR, and DIT were measured by indirect calorimetry in normal training phase and after rapid weight loss. Body composition and energy intake were also measured. [Results] Energy intake significantly decreased in rapid weight loss phase (P<0.05). After the rapid weight reduction, percent reduction of body weight (-4.4%), fat mass (-17.5%), and total body water (-3.2%) significant compare with that of normal training phase (P<0.05). RMR (-15.2%), and SMR (-11.8%) significantly decreased during acute weight loss (P<0.05). DIT (-89.4%) tended to be decrease during acute weight loss. [Conclusion] The present study suggests that rapid weight loss in elite male wrestlers causes decreases in RMR and SMR.